2019
DOI: 10.1186/s13046-019-1428-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA RP11-468E2.5 curtails colorectal cancer cell proliferation and stimulates apoptosis via the JAK/STAT signaling pathway by targeting STAT5 and STAT6

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are tumor-associated biological molecules and have been found to be implicated in the progression of colorectal cancer (CRC). This study aims to examine the effects of lncRNA RP11-468E2.5 and its target genes (STAT5 and STAT6) on the biological activities of CRC cells via the Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling pathway.MethodsWe initially screened the GEO database for differentially expressed lncRNAs related to CRC and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 45 publications
(41 reference statements)
4
70
0
Order By: Relevance
“…LncRNAs, which are encoded by an unstudied region of the human genome, may contain cancer-missing drivers and have attracted attention in recent years as potentially important regulators of carcinogenesis and cancer development. Increasing evidence has indicated that lncR-NAs play an important role in various human diseases, especially in malignant tumors [21][22][23][24]. Antisense long non-coding RNAs, such as TTN-AS1, IDH1-AS1 and AFAP-AS1, have been reported in tumors and closely related to the prognosis, development, invasion and metastasis of tumors [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, which are encoded by an unstudied region of the human genome, may contain cancer-missing drivers and have attracted attention in recent years as potentially important regulators of carcinogenesis and cancer development. Increasing evidence has indicated that lncR-NAs play an important role in various human diseases, especially in malignant tumors [21][22][23][24]. Antisense long non-coding RNAs, such as TTN-AS1, IDH1-AS1 and AFAP-AS1, have been reported in tumors and closely related to the prognosis, development, invasion and metastasis of tumors [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“… 32 The dysregulation of the JAK/STAT signaling pathway has been implicated in the initiation and progression of various cancers, including EC. 33 - 35 Yu et al found that the JAK-STAT pathway was significantly reduced by unbiased RNA sequencing in RNF168-depleted EC cell. Silence of RNF168 reduces JAK-STAT target genes, such as IRF1, IRF9, and IFITM1.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have demonstrated that dysregulated lncRNAs play an important role in the carcinogenesis, development and metastasis of different types of tumor (33)(34)(35). A number of lncRNAs have been reported to be associated with the recurrence, metastasis and resistance to adjuvant therapy of patients with BC (36,37).…”
Section: Discussionmentioning
confidence: 99%